Association between serum cystatin C and early impairment of cardiac function and structure in type 2 diabetes patients with normal renal function. Issue 12 (14th September 2022) - Huang, Zhuoshan; Zhong, Junlin; Zhang, Shaozhao; Xiong, Zhenyu; Huang, Yiquan; Liu, Menghui; Lin, Yifen; Zhong, Xiangbin; Ye, Xiaomin; Zhuang, Xiaodong; Liao, Xinxue
Abstract: Background: Type 2 diabetes mellitus (T2DM) patients may have cardiac remodeling and dysfunction from the early stage of disease. This study aimed to determine the association between cystatin C (CysC) and early cardiac functional or structural impairment in T2DM patients without renal dysfunction. Methods: A total of 1135 T2DM patients without renal dysfunction and known heart diseases were included in our study. Cardiac function and structure were evaluated by echocardiography. Patients were diagnosed as left ventricular hypertrophy (LVH), impaired left ventricular (LV) diastolic function, and categorized into four different LV geometry patterns including normal, concentric remodeling, concentric hypertrophy, and eccentric hypertrophy. Results: In multivariate linear regression analyses, CysC was positively associated with interventricular septum, LV mass index, left atrial volume index, E / e ' ratio, and negatively associated with Tissue Doppler e ', E / A ratio ( p  < .05). As a continuous variable, increasing CysC levels were associated with prevalence of LVH (OR: 1.47, 95% confidence interval [CI]: 1.22–1.77), impaired LV diastolic function (OR: 1.58, 95% CI: 1.33–1.87), concentric hypertrophy (OR: 1.54, 95% CI: 1.23–1.93) and eccentric hypertrophy (OR: 1.34, 95% CI: 1.00–1.80) according to multivariate logistic regression analyses. While as a categorical variable, the highest CysC quartile (CysC > 1.04 mg/L) was associated with LVH (OR: 2.95, 95% CI: 1.74–5.00), impaired LV diastolic function (OR: 4.09, 95% CI: 2.54–6.60), and concentric hypertrophy (OR: 3.26, 95% CI: 2.05–5.18). Conclusions: CysC was significantly associated with early LV remodeling and cardiac functional impairment in T2DM patients with normal renal function. It could be a reliable and convenient biomarker detecting early impairment of cardiac function and structure in T2DM patients.